2004
DOI: 10.1159/000077018
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Psychopathology in a Group of Suicide Attempters

Abstract: Researchers examined the incidence of negative life events and associated these events with psychological scales (depression, hopelessness, self-esteem and state-trait anger) in a group of suicide attempters (n = 101) within the framework of the WHO/EURO Multicenter Study on Suicidal Behavior. Certain negative life events (especially relationship problems and physical/mental abuse in childhood) turned out to be the main indicators of severe mental problems in the family of the attempters (e.g. addiction, self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 13 publications
9
37
2
Order By: Relevance
“…Nevertheless, empirical studies have reported that homicides can also be driven by "nonhostile" motives, as in the case of mercy killings (Websdale 1994;Wilczynski 1997); on the other hand, anger and hatred are not uncommonly identified in suicidal individuals (Cavan 1928;Osvath et al 2004). This study finds that hostility-dominant HS events are different from those where hostility is not identified in almost all aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, empirical studies have reported that homicides can also be driven by "nonhostile" motives, as in the case of mercy killings (Websdale 1994;Wilczynski 1997); on the other hand, anger and hatred are not uncommonly identified in suicidal individuals (Cavan 1928;Osvath et al 2004). This study finds that hostility-dominant HS events are different from those where hostility is not identified in almost all aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eminent stressors, child abuse and adverse family relationships, i.e. problems with parents, are prominent [5,7,13,16,25,[45][46][47] . Goodyer et al [48] specified life events, family dysfunction and friendship difficulties as predictors of persistent major depression in childhood, and a Newcastle research team stressed the perceived impact of life events on childhood depression [49] .…”
Section: Relationships Between Dysfunctional Attitudes Maladaptive Cmentioning
confidence: 99%
“…As other academic medical centers and teaching hospitals adopt a model similar to the one in the current study, the results will prove to be cost-effective. Furthermore, the importance of screening for depression is quite evident, given the fatal result of completed suicide and increased risk for suicide attempts (Angst et al 1999, Osvath et al 2004). In addition, our findings demonstrated significantly worse QOL, health, functioning, and psychiatric symptom severity for depressed patients compared to nondepressed patients.…”
Section: Resultsmentioning
confidence: 99%